Polityka państwowa Ukrainy wobec zapewniania praw polskiej mniejszości narodowej - Krasiwski, Orest; Pidberezhnyk, Nadiia (Studia Europaea Gnesnensia, 2022)
This paper analyses legal guarantees and exercise of rights and freedoms to which the Polish national minority in Ukraine is entitled. In particular, the authors characterize Ukrainian legislation, Ukrainian-Polish bilateral agreements and international treaties which, having been ratified by Ukraine, constitute a commitment to ensuring ethnocultural rights of national minorities, including Poles. All those instruments corroborate that the state policy of protecting national minorities in Ukraine complies with international standards. Further analyses are concerned with the activities of Polish cultural and educational centers and organizations, secondary schools with Polish language of instruction and changes in the functioning of the latter under Ukrainian legislation, demonstrating that one of the priorities of the Ukrainian state policy towards the Polish minority is to protect its national and cultural rights and freedoms.